Effects of preprocedural mouth rinse on microbial load in aerosols produced during the ultrasonic scaling: A randomized controlled trial - Swarga Jyoti Das; Darimeka Kharbuli; Syed Tanwir Alam (Journal of Indian Society of Periodontology, 2022)
Background: During ultrasonic scaling, the harbored microorganisms in the oral cavity get aerosolized, which have important impacts on air quality and can cause a serious health threat to the clinician, patients, and the surroundings. Therefore, this study was conducted to evaluate whether preprocedural mouth rinse has any effect on bacterial load in aerosols generated during ultrasonic scaling. Materials and Methods: A total of 80 subjects with chronic periodontitis were selected and randomly grouped into four comprising twenty in each. The groups were based on the use of preprocedural mouth rinse: no rinse group (control) (A), and test groups with preprocedural mouth rinse with water (B), 0.2% Chlorhexidine gluconate (C), and herbal mouthwash (D). The aerosol produced during ultrasonic scaling was collected on blood agar plates positioned at the chest area of patients, operators, and assistants. Aerosol collected in the operatory before the procedure was considered as baseline. Colonies on the blood agar plates were counted after incubating at 37°C for 24 h. Pairwise comparisons involving positions and mouth rinses on microbial colonies were conducted using independent sample t-test and Tukey's test for post hoc analysis considering 0.05 as the significance level. Results: Microbial colonies were significantly reduced with chlorhexidine gluconate compared to that of others (P < 0.001), followed by herbal mouthwash and water. Again, microbial colonies were highest at the chest area of the operator and lowest at the chest area of the assistant. Conclusions: 0.2% Chlorhexidine gluconate is superior in reducing the microbial load in aerosols produced during ultrasonic scaling.